Ethnic and Gender Differences in Identifying Gifted Students - Sarouphim, Ketty M. (2010)
The purpose of this study was to examine ethnic and gender differences in using DISCOVER, a performance-based assessment, for identifying gifted students. The sample consisted of 941 students from grades K-5 belonging to six ethnicities: White Americans, African-Americans, Hispanics, Native-Americans, South Pacific/Pacific Islanders, and Arabs. The 5 X 6 MANOVA (activity x ethnicity) yielded a significant interaction, but no main effect for either activity or ethnicity was found. Plots of the interaction showed that South Pacific/Pacific Islanders scored highest on Oral Linguistic whereas White Americans scored highest in Math and Native Americans scored highest in Spatial Artistic activity. No gender differences in identification were found. All ethnic groups were well represented among identified students, suggesting that DISCOVER might be used in different countries and with culturally diverse students.